Immunopathogenesis and Immune-based Therapy for Selected Autoimmune Disorders - Aribi, Mourad (IntechOpen, 2017)
The book Immunopathogenesis and Immune-Based Therapy for Selected Autoimmune Disorders is a synthesis work that discusses two main aspects of autoimmunity: Immunopathogenesis and therapeutic approaches essentially based on the immunotherapies. This book deals with different topics on a number of autoimmune disorders, including type 1 diabetes, autoimmune cardiomyopathy, autoimmunity of gastrointestinal tract, systemic sclerosis, and myasthenia gravis. This book will be useful to clinicians, biologists, researchers, teachers, and students who are interested in immunology and immunopathology.